Does blood pressure enhance solute transport in the bone lacunar-canalicular system? - Li, Wen (2010)
Solute transport through bone plays an important role in tissue metabolism and cellular mechanotransduction. Due to limited diffusion within the mineralized bone matrix, both mechanical loading and vascular pressure have been proposed to drive interstitial fluid flow within the lacunar-canalicular system (LCS); thereby augmenting solute diffusion in bone. Although blood supply is critical for bone nutrition, growth, and fracture healing, whether physiological blood pressures can drive significant fluid and solute convection remains controversial within the literature. The goal of this study was to directly test the hypothesis that in vivo blood pressures enhance solute transport in the bone LCS. Using a newly developed imaging approach based on fluorescence recovery after photobleaching (FRAP), we first measured the transport rate of sodium fluorescein (M.W. 376Da) through the tibial LCS in four anesthetized mice (in the presence of vascular pressure). These data were then compared with the tracer transport rates at the same locations/lacunae after sacrifice (in the absence of vascular pressure). Through eighteen paired FRAP experiments we did not detect differences in tracer transport rates between bones from live anesthetized animals versus those in postmortem bodies (p > 0.05). In a separate cohort of four anesthetized mice a mean jugular pulse pressure of ~10 mmHg at ~10 Hz was measured. Further theoretical analysis showed that for bones from both small and large animal species the blood pressure-driven convection of both small (376 Da) and large (43,000Da) molecules was at least one order of magnitude smaller than diffusion under either normal or elevated pressure conditions. We conclude that despite the extreme importance of vasculature in bone physiology, vascular pressure itself does not enhance acute solute transport within the bone LCS. Therefore, mechanisms other than the vascular pressure-induced fluid flow such as altered biochemical factors and/or fluid pressurization may account for the bone adaptation associated with altered circulation. The present study helped clarify a long-standing controversy regarding vascular pressure-induced bone fluid flow and helped provide a better understanding of bone adaptation in both physiological and pathological conditions.